Role of Betatrophin and Inflammation Markers in Type 2 Diabetes Mellitus, Prediabetes and Metabolic Syndrome - Onalan, Erhan; Bozkurt, Ahmet; Gursu, Mehmet Ferit; Yakar, Burkay; Donder, Emir (Coll Physicians & Surgeons Pakistan, 2022)
Objective: To determine the association of betatrophin and inflammation factors in metabolic diseases such as diabetes, impaired fasting glucose, impaired glucose tolerance and metabolic syndrome. Study Design: A cross-sectional, analytical study. Place and Duration of Study: Firat University Medical School between April 2017 and December 2020. Methodology: The study included 20 patients with type 2 diabetes mellitus, 20 patients with impaired fasting glucose (IFG), 20 patients with impaired glucose tolerance (IGT), 20 patients with metabolic syndrome (MetS), and a control group consisting of 20 healthy individuals. Anthropometric, fasting serum biochemical data were collected. Circulating betat-rophin, and inflammation markers were measured by enzyme-linked immunosorbent assay (ELISA). The association of beta-trophin, TNF-alpha, and IL-6 levels between groups were performed with One-way ANOVA and post-hoc Tukey HSD test. Results: Significantly higher levels of circulating betatrophin were observed in IFG, IGT, And MetS groups compared to healthy controls (p=0.017). There were significantly difference TNF-alpha levels in IFG, IGT, and MetS groups compared to healthy controls (p<0.001). The levels of IL-6 were significantly higher in MetS group than healthy controls (p=0.007). Conclusion: The circulating betatrophin and TNF-alpha levels were increased in MetS, IFG and IGT. IL-6 was decreased in MetS compared to the healty controls. Further studies are needed to elucidate the role of betatrophin and inflammatory parame-ters in the development of T2DM and prediabetic syndromes, whether betatrophin could have clinical applications in the development of new antidiabetic agents.
Keywords: Betatrophin; IL-6; TNF-alpha; Metabolic syndrome; Insulin resistance; Diabetes mellitus type 2